THE EFFECT OF THE SEARCH, SOLVE, CREATE, AND SHARE MODEL ON STUDENTS’ SCIENCE PROCESS SKILLS IN MEASUREMENT MATERIAL - Miftahurrahmah, Miftahurrahmah; Darvina, Yenni; Yurnetti, Yurnetti; Novitra, Fuja (PILLAR OF PHYSICS EDUCATION, 2024)
This research aims to determine the impact of using the Search, Solve, Create, and Share (SSCS) learning model on students' science process skills in measurement material. The research method used is a pre-experiment with one group pretest-posttest design. The sample in this study was obtained through simple random sampling technique. Science process skills data were obtained using performance assessments. The results of hypothesis testing using the paired sample t-test can be concluded that th>tt, namely 5.874> 2.056. Based on the statistics, H0 is denied and Hi is accepted, indicating a significant difference between students' average pretest and posttest scores. The rise in student learning outcomes is considered moderate with score 0.304. The effect size test findings received a price of 1.22 which are in the high range. It is possible to conclude that giving treatment using the SSCS learning model has a significant effect on student science process skills on measurement material in the high range.